Analisis pengelolaan kearsipan menggunakan teori daur hidup arsip : Studi Pada Kejaksaan Negeri Batu - Respati, Galuh Ayu; Puspitadewi‎, ‎Ganis Chandra (IJAL (Indonesian Journal of Academic Librarianship), 2023)
The important role of archives in an organization, archives are a source of information and memory center. However, in reality, people are not aware of the importance of archives. The purpose of this study is to determine the description of archive management and the suitability of archive management with the Archives NSPK in the General Crimes of the Batu State Prosecutor's Office. The author chose the research location in the General Crimes of the Batu District Attorney. This type of research utilizes a qualitative descriptive approach. Whereas the sources of data obtained from informants, research locations and supporting documents. Data collection techniques were carried out through interviews, observations, and documentations.The results of the research in the Batu District Attorney's General Crimes archive management using the principle of decentralization. Archive creation occurs manually and through computer data collection. Archival maintenance requires to be checked regularly and transferred to digital media. There is no archive shrinkage so that the archive is left in the storage room. Archival facilities need procurement to support archival activities. Human resources for archive managers ought to participate in archival activities in order to create an organized and systematic archive manager. Records management needs to be adjusted to the NSPK Archives.